Potential influence of the first PCR cycles in real-time comparative gene quantifications - Hege Karin Nogva; Knut Rudi (BioTechniques)
There is an underlying assumption in real-time PCR that the amplification efficiency is equal from the first cycles until a signal can be detected. In this study, we evaluated this assumption by analyzing genes with known gene copy number using real-time PCR comparative gene quantifications. Listeria monocytogenes has six 23S rRNA gene copies and one copy of the hlyA gene. We determined 23S rRNA gene copy numbers between 0.9 and 1.6 relative to hlyA when applying the comparative gene quantification approach. This paper focuses on the first cycles of PCR to explain the difference between known and determined gene copy numbers. Both theoretical and experimental evaluations were done. There are three different products (types 1–3) dominating in the first cycles. Type 1 is the original target, type 2 are undefined long products, while type 3 are products that accumulate during PCR. We evaluated the effects of type 1 and 2 products during the first cycles by cutting the target DNA with a restriction enzyme that cuts outside the boundaries of the PCR products. The digestion resulted in a presumed increased amplification efficiency for type 1 and 2 products. Differences in the amplification efficiencies between type 1, 2, and 3 products may explain part of the error in the gene copy number determinations using real-time PCR comparative gene quantifications. Future applications of real-time PCR quantifications should account for the effect of the first few PCR cycles on the conclusions drawn.